Poor availability of context-specific evidence hampers decision-making in conservation. (August 2020) - Christie, Alec P.; Amano, Tatsuya; Martin, Philip A.; Petrovan, Silviu O.; Shackelford, Gorm E.; Simmons, Benno I.; Smith, Rebecca K.; Williams, David R.; Wordley, Claire F.R.; Sutherland, William J.
Abstract: Evidence-based conservation relies on reliable and relevant evidence. Practitioners often prefer locally relevant studies whose results are more likely to be transferable to the context of planned conservation interventions. To quantify the availability of relevant evidence for amphibian and bird conservation we reviewed Conservation Evidence, a database of quantitative tests of conservation interventions. Studies were geographically clustered, and few locally conducted studies were found in Western sub-Saharan Africa, Russia, South East Asia, and Eastern South America. Globally there were extremely low densities of studies per intervention - fewer than one study within 2000 km of a given location. The availability of relevant evidence was extremely low when we restricted studies to those studying biomes or taxonomic orders containing high percentages of threatened species, compared to the most frequently studied biomes and taxonomic orders. Further constraining the evidence by study design showed that only 17–20% of amphibian and bird studies used reliable designs. Our results highlight the paucity of evidence on the effectiveness of conservation interventions, and the disparity in evidence for local contexts that are frequently studied and those where conservation needs are greatest. Addressing the serious global shortfall in context-specific evidence requires a step change in the frequency of testing conservation interventions, greater use of reliable study designs and standardized metrics, and methodological advances to analyze patchy evidence bases.